2010
DOI: 10.1002/ejlt.201000379
|View full text |Cite
|
Sign up to set email alerts
|

Trans octadecenoic fatty acid (TFA) isomers in German foods and bakery goods

Abstract: In the present study, 122 food samples from the German food market were analysed for their C18:1 trans fatty acid (TFA) content and profile. A particular focus of the survey were baked and fried foods. TFA analysis was performed by means of silver ion SPE (Ag+‐SPE) in combination with high‐resolution GC (HRGC‐FID). Overall, 51 bakery product samples were analysed of which 25 samples were prepacked bakery products purchased from local retail stores and 26 samples of unpacked bakery products purchased from local… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 15 publications
(28 reference statements)
0
6
0
Order By: Relevance
“…In that survey, the highest mean values were also observed in fine bakery products and snacks, cakes and biscuits, with means around 6% and 4%, respectively. In Germany, two recent studies also revealed high amounts of TFA in bakery products and confectioneries, with up to 27% in bakery products in the first ( Fritsche et al., 2010 ), and up to 40% of TFA in the second ( Kuhnt et al., 2011 ). These authors also concluded that unpackaged bakery products had higher amounts of TFA compared to packaged ones, as observed in the present study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In that survey, the highest mean values were also observed in fine bakery products and snacks, cakes and biscuits, with means around 6% and 4%, respectively. In Germany, two recent studies also revealed high amounts of TFA in bakery products and confectioneries, with up to 27% in bakery products in the first ( Fritsche et al., 2010 ), and up to 40% of TFA in the second ( Kuhnt et al., 2011 ). These authors also concluded that unpackaged bakery products had higher amounts of TFA compared to packaged ones, as observed in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…In the absence of a representative national nutrition survey, with ingestion patterns and relative contributions to fat consumption, a preliminary desk review was performed on literature data, aiming to identify the food categories with potentially higher amounts of TFA from industrial origin in other countries ( Hulshof et al., 1999 , Chiara et al., 2003 , Craig-Schmidt, 2006 , Stender et al., 2006 , Baylin et al., 2007 , Ledoux et al., 2007 , Griguol et al., 2007 , Wagner et al., 2008 , Richter et al., 2009 , Fritsche et al., 2010 , Remig et al., 2010 , Cakmak et al., 2011 ; Hissanaga et al., 2012 , Roe et al., 2013 , Saunders et al., 2008 ). The following food categories were selected: bakery/breakfast cereals, biscuits/wafers/cookies, bouillon cubes, butter, chocolate snacks, chocolate spreads, fast food, instant desserts, instant soups, margarines/shortenings, pastry, popcorn, and potato chips/French fries.…”
Section: Methodsmentioning
confidence: 99%
“…In the last few years, however, the use of industrially produced TFAs has dramatically decreased in Switzerland , Austria , Germany , the United States , and Canada . In practically all food products iTFAs showed a decline except for certain foods such as cookies, biscuits, bakery products, cake mixes, shortenings, and frozen foods that still contain high amounts of TFAs in some regions of the world.…”
Section: Occurrence Of Trans Fatty Acidsmentioning
confidence: 99%
“…In 2008, the German Federal Office of Consumer Protection and Food Safety (BVL) analyzed bakery products from German bakeries and found an average TFA content of 12.8% of the total fat in 40 out of 74 donuts and certain pastries [9]. These findings were confirmed by Fritsche et al [10,11] who determined TFA contents of sometimes more than 25% of total fat in deep-fried bakery products purchased from local artisan bakeries. Likewise, Br€ uhl and Unbehend [12] determined TFA levels of at least 25-32 g/100 g in donuts deep-fried in PHPO containing 42.5% TFA.…”
Section: Introductionmentioning
confidence: 91%